High-intensity interval training modifies energy supply in male artistic gymnastics and improves floor-specific but not pommel horse-specific endurance performance - Seemann-Sinn, Alexander; Rüdrich, Peter; Sandau, Ingo; Naundorf, Falk; Wolfarth, Bernd (Frontiers in Sports and Active Living, 2025)
IntroductionWell-developed specific endurance performance in artistic gymnastics is a crucial foundation of successful performance. Therefore, the identification of effective training programs for gymnastics-specific endurance performance is an important factor. This study aims to analyze the effectiveness of high-intensity interval training (HIIT) on gymnastics-specific endurance performance and changes in energy supply during floor and pommel horse routines.MethodsTwenty-five male artistic gymnasts (age: 15.0 ± 1.5 years; weight: 51.2 ± 10.6 kg; height: 160.0 ± 10.4 cm) were allocated to either the experimental (n = 14) or the control group (n = 11). For 6 weeks, the intervention group completed a HIIT two times a week, integrated into the normal gymnastics training. The control group performed normal gymnastics training, including their routine programs for physical fitness development. Floor- and pommel horse-specific endurance performance was determined by the mean jump height in a repeated jump test and by the maximum number of circles in a circle test. Energy supply on the floor and pommel horse was calculated using mobile spiroergometry and the PCr-LA-O2 method.ResultsThe gain score analysis showed a significantly greater improvement in mean jump height for the intervention group, but no significant effect for the maximum number of circles. In terms of energy supply, the intervention group showed a significantly greater increase in aerobic metabolism on the floor and pommel horse. Additional correlation analyses show relationships between physiological parameters (O2 deficit and VO2 kinetics) and endurance performance as well as the modification of energy supply.ConclusionThe results of the study show that 6 weeks of semi-specific HIIT can improve floor-specific endurance performance and increase the aerobic metabolism during floor and pommel horse routines. Faster VO2 kinetics and the associated lower O2 deficit seem to be important physiological parameters for these improvements.